Stem Cells on the Brain: Modeling Neurodevelopmental and Neurodegenerative Diseases Using Human Induced Pluripotent Stem Cells - Priya Srikanth; Tracy L. Young‐Pearse (2014)
Seven years have passed since the initial report of the generation of induced pluripotent stem cells (iPSCs) from adult human somatic cells, and in the intervening time the field of neuroscience has developed numerous disease models using this technology. Here, we review progress in the field and describe both the advantages and potential pitfalls of modeling neurodegenerative and neurodevelopmental diseases using this technology. We include tables with information on neural differentiation protocols and studies that developed human iPSC lines to model neurological diseases. We also discuss how one can: investigate effects of genetic mutations with iPSCs, examine cell fate-specific phenotypes, best determine the specificity of a phenotype, and bring in vivo relevance to this in vitro technique.